Field Test Study of the Artificial Ground-Freezing Method Subsurface Excavation Construction of Watered Sandy Stratum in Collapsible Loess Area - Yuan Mei; Liangjie Zhao; Xueyan Wang; Dongbo Zhou; Tong Yang; Yuanying Liu; Hang Gong (Advances in Civil Engineering)
Saturated sandy stratum often makes tunnel excavation exceedingly difficult owing to its high water content. The artificial ground-freezing (AGF) method is an effective way to reduce the construction risks in such stratum; however, the AGF mechanism in the saturated sandy stratum of a collapsible loess area still lacks sufficient research. Based on field tests and numerical simulations, this study investigates the regularity of the temperature development, frost heave, and thaw subsidence distribution during the cross passage construction of a saturated sandy stratum in a collapsible loess area, using the AGF method. The results showed that the inward development rate of the frozen soil wall in the saturated sandy stratum was faster than its outward development rate. The gradient of the soil cooling curve was positively related to the longitudinal depth of the cross passage. The thickness of the frozen soil wall calculated by the slowest development rate of the frozen soil was conservative. The application of the pressure relief hole was beneficial to the release of the frost-heaving force and the control of the frost-heaving displacement. The pressure gauge pressure increase could be used as an identifier for the closure of a frozen soil wall. After excavation, the inner wall of the cross passage moved toward the inner space of the passage.